The Effect Of Integrated Emergency Management System Education In Stroke Emergency Using Booklets On Community Knowledge - renny Triwijayanti; Triara Junior; Feby Puryanti (Fakultas Kesehatan IKesT Muhammadiyah Palembang, 2023)
Background : Pre-hospital stroke management is a service provided at the time and during the first time the victim is found, during the transportation process until the patient arrives home Sick. Pre- hospital stroke treatment can be determinants of condition and treatment furthermore. Public must own knowledge in do action pre-hospital strokes. Efforts that can be made to increase public knowledge are wrong One way is to provide health education. Method: This type of research is analytic descriptive research by collecting data using a questionnaire, and data analysis Which done is analysis univariate And bivariate, participant in activity research This as many as 25 respondents, with the variable Integrated Emergency Management System Education On Emergency Strokes Use booklet To Knowledge Public. This research was conducted in the working area of the Tanjung Enim Public Health Center in April - May 2023, Results: The results showed that there were significant differences in anxiety between before and after the intervention on health education The Effect of Education System Countermeasures bad Emergency Integrated On Emergency Strokes Use booklet To Knowledge Public, Obtained mark p <0.05. Discussion : Research which includes interpretation and discussion of research results as described in the previous chapter. The explanation is based on research objectives and hypotheses, research limitations related to the process of implementing research on nursing services, nursing science and education as well as the objectives of research interests and the implications of research results for services and research in the nursing area